Time Shifting and Agile Time Boxes in Course Design - Anders Norberg (Athabasca University Press, 2017)
The ongoing integration of Information and Communication Technologies (ICTs) into higher education courses is often called blended learning although it often relates to course design. It is usually understood in place categories, as a combination of traditional classroom-based sessions and Internet-enabled distance or online learning practices. One alternative understanding of ICT integration can be constructed of time categories, with an understanding of ICTs more as process- and project-related. Two such design frameworks are conceptually presented and then used together in a small case study in a pilot experiment in physics at the preparatory level for entering engineering programs at a university in Northern Sweden. These are a) time shift mechanisms between synchronous and asynchronous learning modes in the course process and b) agile frameworks mechanisms adapted from work process developments in the software industry. Both are here used to address common procrastination problems in flexible education. Data were collected in student interviews and analysed with qualitative content analysis. Results show student satisfaction with the work rhythm and that a feeling of presence, which enables easy interaction, can be facilitated by synchronicity.